Style and genre differentiation of mass-media speech in modern linguistic (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article deals with problem of functional-style status of mass-media speech, inwardstylistic distribution of informative and publicistic styles, the perspectives of investigation of informative and publicistic genres connecting with activation of public-political life are also determined in the article.
Keywords: the language of mass-media; informative style; publicistic style; genre